Acoustic evidence of hydrocarbon release associated with the Spitsbergen Transform Fault, north of the Molloy Ridge, Fram Strait - Chand, Shyam; Knies, Jochen; Geissler, Wolfram H.; Plaza-Faverola, Andreia; Thorsnes, Terje (Frontiers in Earth Science, 2024)
Hydrocarbon gases formed from biotic and abiotic processes are released through the seafloor at different locations around the world. They have been widely observed directly in video and photo data, and indirectly on echosounder data. Even though biotic gas generation is a very common process, abiotic gas generation is limited to regions where serpentinization of ultramafic rocks occur. Indications of abiotic gas occurrences are therefore sparse and much speculated. Here, we investigated the Spitsbergen Transform Fault, the Molloy Ridge, the Molloy Deep, and the Molloy Transform Fault/Fracture Zone, (a transform fault-bounded pull-a-part region offshore western Svalbard) where both processes may be active. Multiple acoustic gas flares, ~1770m and ~3355m high above the seafloor (tallest ever recorded), were observed indicating active migration and seepage of hydrocarbons. The proximity to the mid oceanic ridge and the documented high heat flow suggests the influence of high temperatures 2 on organic-rich sedimentary deposits. Deep seismic data and other geological information available indicate that the main source of gas could be from thermal cracking of either pre-or syn-rift source rock organic material, potentially mixed with methane from serpentinization of mantle rocks (peridotites). Correlation with seismic stratigraphy from Ocean Drilling Program (ODP) Sites 910 and 912 on the adjacent Yermak Plateau suggests that these sedimentary source rocks may be present at the northern flank of the Molloy Ridge and within the deep graben along the Spitsbergen Transform Fault. The ~3 km thick sedimentary succession in high heat flow zones within the transform fault and the active bounding faults allow generation and migration of hydrocarbons to the seafloor and sustains present day seepage.